Variation in project management practices across borders. Issue 13 (3rd October 2022) - Zwikael, Ofer; Pathak, Raghuvar Dutt; Ling, Florence Y. Y.; Titov, Sergei; Husain, Zafar; Sharma, Bhavya; Tay, Chin Yang; Samson, Danny
Abstract: As project teams become more global and culturally diverse, it is important for project managers to understand how various project management practices are implemented in different countries. We use hierarchical linear modelling to explore variation in project management practices among seven countries using GLOBE dimensions of these countries to understand patterns. Of the nine GLOBE dimensions, two particular elements had an impact on project management practices. Performance orientation has a significant positive influence and gender egalitarianism had a significant negative impact on the adoption of project management practices. Practical implications include that for those two specific GLOBE factors, executives and project team leaders should use such knowledge to anticipate how they will impact on the natural tendencies of project team members in various countries, Further, when operating projects with international team membership, such as global virtual teams, this study illuminates that some cultural differences might lead to differences in style and practice of project team members, requiring cognizant and careful team leadership. The article contributes to theory by showing that only some and not all aspects of national culture impact on project management practices that are theoretically deemed attractive as part of project management's body of knowledge.